ANALISIS FAKTOR- FAKTOR YANG MEMPENGARUHI STRUKTUR MODAL (STUDI EMPIRIS PADA PERUSAHAAN PERTAMBANGAN YANG LISTING DI BEI TAHUN 2010-2013) - Fajar Jias Nugroho; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2015)
This research is aimed to analyze the factors that affect the capital structure on a mining company listed on the Indonesia Stock Exchange. The sample of this research is a mining company that is listed on the Indonesia Stock Exchange in the year 2010-2013. The population of this research are 36 by using purposive sampling method companies. These datas were analyzed using multiple regression analysis model, which is preceded by the classical assumption that consists of normality test, heteroscedasticity, multicollinearity and autocorrelation test. Hypothesis testing is done by using the F test and t test. The results of this research indicate that profitability, and business risks have a significant effect the company's capital structure. While the asset structure, ownership structure, company size, sales growth and the tax rate does not have a significant effect on the Capital structure.